2012
DOI: 10.5505/tjtes.2012.90767
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament injuries: do affect surgical treatment with otograft and allograft options, clinical results?

Abstract: AMAÇBu çalışmada, allogreft ya da otogreft ile ön çapraz bağ (ÖÇB) rekonstrüksiyonun klinik sonuçları araştırıldı. GEREÇ VE YÖNTEMAnterior tibial tendon (ATT) allogreft (n=52) ya da dörtlü hamstring (DHT) otogreft (n=30) ile ön çapraz bağ (ÖÇB) rekonstrüksiyonu uygulanan 82 hastanın sonuçları geriye dönük olarak değerlendirildi. Hastalar son kontrolde, Uluslararası Diz Dokümantasyon Komitesi'nin (IKDC) diz skoru ve Lysholm skoru, performans (tek bacak zıplama) ve laksite (pivot-shift, Lachman, öne çekmece) tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“… 5 , 10 , 18 , 23 - 25 , 32 , 38 , 42 , 49 , 56 , 61 , 62 , 66 , 76 , 78 - 80 , 83 Twenty-one studies were excluded because duration of follow-up was less than 2 years. 1 , 13 , 14 , 31 , 35 , 39 - 41 , 43 , 51 , 52 , 58 , 65 , 70 , 73 , 75 , 84 , 87 , 89 - 91 Three studies were excluded because they did not report on failure (2 reported on muscle strength and 1 on transplantation safety). 37 , 50 , 55 One study was excluded for not meeting the minimum treatment arm size of 15 patients.…”
Section: Resultsmentioning
confidence: 99%
“… 5 , 10 , 18 , 23 - 25 , 32 , 38 , 42 , 49 , 56 , 61 , 62 , 66 , 76 , 78 - 80 , 83 Twenty-one studies were excluded because duration of follow-up was less than 2 years. 1 , 13 , 14 , 31 , 35 , 39 - 41 , 43 , 51 , 52 , 58 , 65 , 70 , 73 , 75 , 84 , 87 , 89 - 91 Three studies were excluded because they did not report on failure (2 reported on muscle strength and 1 on transplantation safety). 37 , 50 , 55 One study was excluded for not meeting the minimum treatment arm size of 15 patients.…”
Section: Resultsmentioning
confidence: 99%
“…12,13,22 However, the rate of graft incorporation and remodeling are slower for allograft than for autograft. 10,28 The incidence of chronic knee effusion after allograft reconstruction diminishes. 10,28 The incidence of chronic knee effusion after allograft reconstruction diminishes.…”
Section: Allograftsmentioning
confidence: 99%
“…12 Clinical studies with 5-year and 7-year follow-up have demonstrated that the outcomes of early ACL allograft reconstructions are similar to those of the autografts. 10,28 A variety of tendon allografts such as bone-patellar tendon-bone, Achilles tendon, anterior tibialis, fascia lata, and hamstring tendons have been used for ACL reconstructive surgery. This is perhaps because of the improved allograft procurement and avoidance of ethylene oxide sterilization in the new tissue preparation technologies.…”
Section: Allograftsmentioning
confidence: 99%
See 2 more Smart Citations